Formulation Of Tomato Fruit Extract (Solanum Lycopersicum L.) Facial Toner With Variations In Surfactants - Diputra, Angga Anugra; Nurfatimah, Vivi (Syntax Corporation Indonesia, 2025)
Toner is a facial care product used to cleanse the skin of dirt and refresh the face. Tomatoes (Solanum lycopersicum L.) are a natural source of antioxidants rich in vitamin A, vitamin C, beta-carotene, potassium, and lycopene. The objective of this study was to formulate a facial toner made from tomato fruit extract by observing the effect of varying surfactant concentrations on the formulation. This research was conducted experimentally. Four toner formulations were made with varying surfactant concentrations: F0 (0%), F1 (5%), F2 (7.5%), and F3 (10%). The resulting toners were then tested for stability over 6 cycles using the cycling test method. The evaluation of these formulations included organoleptic testing, homogeneity testing, viscosity testing, and pH testing. The results of the study of facial toner formulations of tomato fruit extract (Solanum lycopersicum L.) with variations in surfactant concentrations in F1 and F2 showed that the formulations were stable in organoleptic tests, homogeneity tests, and pH tests but were not stable in viscosity tests, while F0 and F3 only met the requirements for pH testing. The conclusion from the results of all cycles in the stability test was that variations in surfactant concentration affected the physical stability of the toner formulation. Based on the study, there was no stable formula.